CATALOGUE OF AQUATIC MITES FROM THE MINHO RIVER (NW IBERIAN PENINSULA) (Environmental Smoke, 2021)
Acari are a subclass of chelicerate arthropods that includes mites and ticks. The present study focuses on the taxonomic diversity of aquatic mites in the Portuguese territory of the Minho Region. Our aim was to compile all available information and thus generate a list of species linking them to the site where they were recorded. Aquatic species were all those that live exclusively in the marine environment, deep sea, intertidal, freshwater, brackish water or in transitional environments with the terrestrial environment if their lifestyle is associated with the aquatic environment. Since the first records of Portuguese endemic mites by Lunblad in the 1950s several authors have contributed to accurately catalogue, record, and redescribe this vast group in Portugal and Minho consecutively. In our review in this work, we used the Global Biodiversity Information Facility (GBIF) to obtain previous occurrences supplemented by an extensive literature review and the book collection Süßwasserfauna von Mitteleuropa, among others. Additionally, we resorted to active sampling and by-catch sampling in the Portuguese section of the Rio Minho catchment area. The collected organisms represent 12 new records for the Minho River and among them 10 are new records for Portugal, which were deposited in the Natural History Museum of the Iberian Peninsula - NatMIP (“Museu de História Natural da Península Ibérica”), Vila Nova de Cerveira, Portugal.